Financial Performance Comparison (Empiric Study on Conventional Commercial Banks and Sharia Commercial Banks 2012-2018) - Akhmadi Akhmadi Akhmadi; Ernis Chaerunisa; Shinta Zahra Chaerunisa (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
This study aims to examine more the comparison of financial performance between Islamic Commercial Banks and Conventional Commercial Banks. The population in this study includes conventional banking companies and Islamic banking which are listed on the Indonesia Stock Exchange and supervised by the Financial Services Authority (OJK) for the period 2012-2018 as many as 114 companies. The observational data used were 56 data from 14 general and Islamic banks which were sampled in this study. The method of analysis used the normality test, the independent sample t-test, and the Mann-Whitney test. The results showed that tThere is no significant difference in the Capital Adequency Ratio between Conventional Commercial Banks and Islamic Commercial Banks, There is a significant difference in non-performing loans / financing (NPL / NPF) between Conventional Commercial Banks and Islamic Commercial Banks, there is a significant difference in return on assets (ROA) between Commercial Banks Conventional with Islamic Commercial Banks, there is a significant difference in operating expenses to operating revenue (BOPO) between Conventional Commercial Banks and Islamic Commercial Banks, there is a significant difference in loan / financing to deposit ratio between Conventional Commercial Banks and Shari'ah Commercial Banks.